IMPLEMENTASI SISTEM PEMANTAUAN SUHU DAN KELEMBABAN UDARA BERBASIS IOT PADA PLANT FACTORY KEBUN PERCOBAAN FAKULTAS PERTANIAN UNIVERSITAS UDAYANA - I Nyoman Agus Junaedi; Anak Agung Ngurah Amrita; I Nyoman Setiawan (Jurnal SPEKTRUM, 2022)
Plant factory is a technological development in agriculture that is able to overcome the decline in productivity in the agricultural sector caused by limited agricultural land. The concept of the plant factory itself is the application of a good environmental condition for plants to grow indoors which is easy to control so that they are not affected by the weather outside. The temperature and humidity in the plant factory must be monitored and controlled in real time with an Internet of Things (IoT) technology that utilizes internet connectivity to connect and transmit data. The system is designed using two microcontrollers, namely Arduino nano which functions as an input reader for temperature and humidity sensors, namely the DHT22 sensor, while ESP32 functions as a module for sending DHT22 sensor data to the Blynk via an internet connection to be stored in the database and can be accessed via the smartphone user. The ESP32 also functions as an automatic control of air humidity and air conditioning (AC) control remotely via a smartphone.